Behavioral risk factors for NCDs among school children in the National Capital Region (NCR), Philippines - Endrina-Ignacio, Ma. Socorro (2018)
The Philippines is experiencing rapid nutrition transition found to be associated with increased rates of non-communicable diseases (NCDs) attributed to ?modifiable? risk behaviors i.e., tobacco use, unhealthy diet, insufficient physical activity, and the harmful use of alcohol. NCDs have not spared the young people, especially the urban residents. This cross-sectional study was conducted to establish baseline data on NCD related behavioral risk factors and consumption of ultra-processed foods (UPF) among school children aged 10?17 years old in the Philippine Red Cross? (PRC) selected pilot schools in Manila and Quezon City (QC), National Capital Region (NCR). It also aims to determine the students? awareness of the main causes of NCDs, source of information on NCDs, awareness of school policies, and participation in activities on NCD prevention. Qualitative methods using structured and food frequency questionnaires were employed to obtain information from 1665 randomly selected students in the study schools. NCD risk behaviors were noted among the students ? with 74% of 31 students already smoking more than 3 sticks of cigarettes daily, 55% of 94 students already drinking alcohol once a month, and only 27?38% of 1665 students engaged in daily physical activity. High proportions of students have consumed fatty foods (83%), sugary foods (75%), and salty foods (57%) in the past 7 days at the time of the interview. NCD information were obtained from TV (90%), social media (78%), and peers (41%). Sixty percent (60%) were aware of NCD related school policies and 32.5% have received NCD related materials. The prevalence of NCD behavioral risk factors warrants a strong partnership between the school and the community to promote healthy diet and lifestyle practices.